THE NESTING PRINCIPLE OF CLASSIFICATION OF ACHROMATIC COLOR DERIVATIVES (ON THE MATERIAL OF STEPAN PROTSIUK’S PSYCHOLOGICALLY BIOGRAPHICAL NOVELS) - Шитик, Людмила; Маслюк, Наталія (Linguistic Bulletin (Movoznavchyi Visnyk), 2020)
Summary. Introduction. Modern derivatology seeks to systematically analyze the processes of word formation, taking into account the role of the forming basis and derivative formant, which involves the application of the nesting approach. The research base is actively supplemented by the works of postmodern discourse, which are sufficiently represented by the name of colors and their derivatives. Purpose. The purpose of the article is to comprehensively analyze achromatic color derivatives in Stepan Protsyuk’s psychologically biographical novels according to the nesting principle. Methods. To achieve this goal involved the following methods: linguistic description, method of component and contextual analysis, linear and nonlinear methods of derivation. Results. The nesting principle of classification represented in the work made it possible to characterize not only derivative but also semantic features of derivative words, ensured clarification of the word-forming potential of basic colors. Eight word forming nests denoting achromatic colors with non-derivative nucleus such as білий, чорний, блідий, сірий, темний, рябий, сивий and the derivative nuclei (світ)лий are differentiated. All word-forming nests are characterized by the quantitative and qualitative composition of the nomenclature, the degree of derivation (tacts) and the productivity of the ways of word-building. The derivative words are arranged according to the part of speech in the following order: adjectives, nouns, verbs, adverbs, compound words, where the component is achromatic color. Word-formative means are defined for each color derivative. The results of the research are presented in tables. Originality. The originality of the scientific research lies in the complex analysis of word-forming nests of achromatic colors in Stepan Protsіuk’s psychologically biographical novels about Ukrainian writers – Vasyl Stefanyk («The rose of ritual pain») and Arkhyp Teslenko («Black Apple»). Conclusion. It is concluded that the lexical-semantic group of achromatic colors in S. Protsyuk’s novels has a diverse structure. Each word-forming nest is analyzed according to the degree of derivation (tact) and productivity of the word-building way, presented in the form of a table. The productivity of the word-building ways was determined: suffixation (53%), compounding (29%), prefixation (15%), postfixation (1,5%), non-affixation (1,5%). By morphological principle, four types of color derivatives are distinguished: derivative adjectives, different forms of verbs, nouns, adverbs. The word-formative chains and pairs are characterized, the word-forming and semantic changes of the color derivatives are described. Examples of the use of new colors in the novels are given. We see the prospect of further scientific research in the study of chromatic color derivatives by the nesting principle.